Upaya Mengembangkan Kompetensi Guru Penggerak di Sekolah Dasar Pada Kurikulum Merdeka Belajar - Novela Aditiya; Siti Fatonah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
Curriculum changes that occurred during the Covid-19 pandemic made the government reformulate the existing national education “Kurikulum 2013” to become “Merdeka Belajar” Curriculum (independent learning). The schools and teachers became the important institutions in the Independent Learning Curriculum that focused on the character of the Pancasila Students Profile. The teacher competencies need to be improved to achieve the learning objectives through the Sekolah dan Guru Penggerak (the activator schools and teachers). The role of the activator teachers was to improve the teachers’ quality in implementing the Independent Learning Curriculum. The purpose of this study is to determine the efforts of the teachers in improving their competence through the predicate of the Activator Schools. The research was conducted referring to a descriptive qualitative approach. The research was carried out at one Activator School, which was the Elementary School 4 Koba in the Koba district. The purposive sampling technique was used. The primary data sources were obtained through observations and discussions with 7 female teachers in low and high grades. Meanwhile, the secondary data sources were obtained from the previous studies from international, Sinta 1, and Sinta 2 journal articles. The interview process was done in a semi-structured way by providing a form, then the data results were analyzed by reducing and concluding. The results of this study revealed that the activator school sought to develop learning activities that realizes the characters of Pancasila to the students. The components that needed improvements was the teachers’ ability to do innovation in the lesson plan that contains the characters of Pancasila. The concerns faced by the activator teachers was that the training activities were carried out online in a short time, that reduced the opportunity to train making indicators and the implementation. It is suggested the school look for information from relevant education agency sources.